2020
DOI: 10.1002/ange.202009323
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Promoted Copper‐Catalyzed Enantioselective Alkylation of Azoles

Abstract: A catalytic asymmetric alkylation of azoles with secondary 1-arylalkyl bromides through direct C À H functionalization is reported. Under blue-light photoexcitation, a copper(I)/carbazole-based bisoxazoline (CbzBox) catalytic system exhibits good reactivity and high stereoselectivity, thus offering an efficient strategy for the construction of chiral alkyl azoles. These reactions proceed at low temperature and are compatible with a wide range of azoles. Scheme 1. Alkylation of azoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…21 It is important to mention that two catalytic cycles are merged in this reaction: while LCu I OPh served as the photocatalyst (Scheme 2, mode C), the enantioselective C− N formation step was mediated by a chiral diamine ligand- ) cross-coupling of secondary (hetero)benzyl bromides with azoles. 22 Their mechanistic study showed that the nucleophile-sequestered copper complex serves as the photoactive species for the reaction initiation.…”
Section: Photoinduced Enantioconvergent Radical Cross-couplingmentioning
confidence: 99%
“…21 It is important to mention that two catalytic cycles are merged in this reaction: while LCu I OPh served as the photocatalyst (Scheme 2, mode C), the enantioselective C− N formation step was mediated by a chiral diamine ligand- ) cross-coupling of secondary (hetero)benzyl bromides with azoles. 22 Their mechanistic study showed that the nucleophile-sequestered copper complex serves as the photoactive species for the reaction initiation.…”
Section: Photoinduced Enantioconvergent Radical Cross-couplingmentioning
confidence: 99%
“…Visible-light-driven catalysis has emerged as a powerful tool for the construction and functionalization of structurally diverse compounds in organic synthesis . The combination of photoredox and transition-metal catalysis expands the scope of coupling partners by alternating the reaction pathways . The photocatalytic reaction always starts with excitation of the photocatalyst by visible light, which usually gets one electron from the reagents through a single electron transfer (SET) process to initiate the reaction .…”
Section: Introductionmentioning
confidence: 99%
“…Pioneered by the work of Fu and co-workers on photoinduced copper-catalyzed enantioselective cross-coupling reactions [28], the groups of Gong [29,30], Zhang [31] and Liu [32] recently contributed to the emergence of this research field by describing enantioselective alkylation of imine, dual carbofunctionalization of alkenes and decarboxylative alkynylation with terminal alkynes, respectively. The most recent example was reported in 2021 by Zhang and coworkers, who developed an asymmetric alkylation of azoles catalyzed by a copper(I)/carbazole-based oxazoline ligand system under visible light irradiation (Figure 1d) [33]. A large variety of azoles and secondary 1-arylalkyl bromide substrates were efficiently engaged in this asymmetric photocatalytic C-H functionalization process to afford the desired chiral alkylated azole products in good yields and up to excellent enantioselectivity.…”
mentioning
confidence: 99%